Abdominal muscle and quadriceps strength in chronic obstructive pulmonary disease. Issue 9 (27th May 2005) - Man, W D-C; Hopkinson, N S; Harraf, F; Nikoletou, D; Polkey, M I; Moxham, J
Abstract : Background: Quadriceps muscle weakness is common in chronic obstructive pulmonary disease (COPD) but is not observed in a small hand muscle (adductor pollicis). Although this could be explained by reduced activity in the quadriceps, the observation could also be explained by anatomical location of the muscle or fibre type composition. However, the abdominal muscles are of a similar anatomical and fibre type distribution to the quadriceps, although they remain active in COPD. Cough gastric pressure is a recently described technique that assesses abdominal muscle (and hence expiratory muscle) strength more accurately than traditional techniques. A study was undertaken to test the hypothesis that more severe weakness exists in the quadriceps than in the abdominal muscles of patients with COPD compared with healthy elderly controls. Methods: Maximum cough gastric pressure and quadriceps isometric strength were measured in 43 patients with stable COPD and 25 healthy elderly volunteers matched for anthropometric variables. Results: Despite a significant reduction in mean quadriceps strength (29.9 kg v 41.2 kg; 95% CI −17.9 to −4.6; p = 0.001), cough gastric pressure was preserved in patients with COPD (227.3 cm H2 O v 204.8 cm H2 O; 95% CI −5.4 to 50.6; p = 0.11). Conclusions: Abdominal muscle strength is preserved in stable COPD outpatients in the presence of quadriceps weakness. This suggests that anatomical location and fibre type cannot explain quadriceps weakness in COPD. By inference, we conclude that disuse and consequent deconditioning are important factors in the development of quadriceps muscle weakness in COPD patients, or that activity protects the abdominal muscles from possible systemic myopathic processes.